PENERAPAN ASAS EQUALITY BEFORE THE LAW DALAM KASUS TINDAK PIDANA PENCABULAN - Kadek Dedy Suryana; Putu Angga Sarmawan (Jurnal Ilmiah Raad Kertha, 2021)
Obscenity is a crime that attacks the honor of decency and is against morals and religion. Because obscenity is a violation of human rights that often occurs and there is no justification for it. Obscenity is an act that is condemned by the community and it can happen from those who have very close family relationships or close relatives with the victim. Nowadays cases of sexual abuse also involve elements of the sulinggih. Sulinggih is a person who has received purification through a ceremony called madiksa. A walaka who has been educated gets a position as a sulinggih or sadhaka. The problems that will be investigated by the author are 1) How is the regulation of the application of the principle of equality before the law in the case of criminal acts of sexual abuse by unscrupulous persons? The objectives of this research are as follows, among others, to determine the regulation of the application of the principle of equality before the law in the case of the criminal act of sexual abuse by unscrupulous individuals. The type of research used is a normative legal research type, namely by reviewing or analyzing legal materials from the literature or books and laws and regulations related to the research that will be discussed. The results of this study are the regulation of the application of the principle of equality before the law in the case of the criminal act of sexual abuse by unscrupulous individuals who are regulated in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia which affirms that all citizens have the same position under the law, which is further regulated in the Act. -Law Number 48 of 2009 concerning Judicial Power article 4 (1) which states that the Court will judge according to the law without discriminating against people. Legal sanctions for criminal acts Obscenity is regulated in Articles 289 to 296 of the Criminal Code. Article 290 of the Criminal Code, namely: Whoever commits an obscene act with a person, even though he knows that the person is unconscious or incapacitated, whoever commits an obscene act with someone even though he knows or should have guessed that his age is not yet fifteen years or if the age is not clear, the person concerned is not yet ready for marriage, and whoever persuades someone whom he knows or should reasonably suspect that he is not yet fifteen years old or if his age is not clear, the person concerned is not yet ready for marriage, to commit or allow an act to be committed. obscene or have sex outside of marriage with another person